Peran Pemerintah dalam Upaya Pemenuhan Hak Atas Pelayanan Kesehatan melalui Penyediaan Obat Murah bagi Masyarakat - Yuliana Primawardani (Badan Strategi Kebijakan Hukum, 2013)
Health is one of the rights possessed by humans since birth. Efforts to comply with the health of any human rights as citizens is done through the provision of health services in order to achieve optimal health status for the community. One is to provide health services to the community, either in the form of health care in the form of free or cheap drug supply for the community. Provision of cheap drugs in the market, only intended for certain types of diseases. For other diseases, pharma prices are still relatively expensive. While not everyone can afford to buy drugs at a great price. It is therefore very necessary role of government in providing health services, including by providing cheap drugs to the community.